2011
DOI: 10.1007/s11011-011-9251-0
|View full text |Cite
|
Sign up to set email alerts
|

Absence of neuropsychological impairment in hyperammonaemia in healthy young adults; possible synergism in development of hepatic encephalopathy (HE) symptoms?

Abstract: The aetiology of minimal hepatic encephalopathy (mHE) remains unclear. It is generally accepted that hyperammonaemia plays a major role, however there are a multitude of metabolic perturbations present. To determine the contribution of hyperammonaemia to mHE symptom development, ten healthy males (Age:25 ± 5 yrs, BM:76.3 ± 7.1 kg, Height:178.6 ± 4.5 cm, mean ± SD) received two 4 h intravenous infusions of either a 2% ammonium chloride solution (AMM) or a placebo (PLA;0.9% sodium chloride) using a double blind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…This result is also consistent with the observation that dogs with urea cycle enzyme deficiency have increased plasma ammonia concentrations but do not typically developing clinical signs of HE [34]. It is also supported by the finding that humans, when administered ammonium chloride, do not develop classical signs of HE [35]. …”
Section: Discussionsupporting
confidence: 89%
“…This result is also consistent with the observation that dogs with urea cycle enzyme deficiency have increased plasma ammonia concentrations but do not typically developing clinical signs of HE [34]. It is also supported by the finding that humans, when administered ammonium chloride, do not develop classical signs of HE [35]. …”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, whether a correlation exists between hyperammonemia and HE severity in CLF still remains controversial [11], [12], [13], [14] and [15]. A recent study demonstrated that ammonia administered intravenously to healthy volunteers did not cause any significant neuropsychological impairment [16], supporting the premise that pathogenic factors other than ammonia are involved in the pathogenesis of brain edema and HE in CLF.…”
mentioning
confidence: 99%
“…Further clinical studies are on their way testing the possible benefit of H3R antagonists in other neurodegenerative diseases characterized by fatigue and day‐time sleepiness. Although not accompanied by neurodegeneration, hyperammonemic conditions are associated with fatigue especially during extreme exercise or liver pathology . Thus, patients suffering from hyperammonemia may benefit from symptomatic treatment with H3R antagonists/inverse agonists.…”
Section: Introductionmentioning
confidence: 99%
“…Although not accompanied by neurodegeneration, hyperammonemic conditions are associated with fatigue especially during extreme exercise or liver pathology. 4,5 Thus, patients suffering from hyperammonemia may benefit from symptomatic treatment with H3R antagonists/inverse agonists.…”
mentioning
confidence: 99%